2002
DOI: 10.1023/a:1023206620304
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Chemical composition of the sponge Chondrosia reniformis from the / Canary Islands Jordan ~e c h e v ' , William W. ~hristie', Rafael ~obaina', Fernando M. de ~i e~o~, Albena 1vanova4, Simeon ~o~o v ' & Kamen stefanov1>* 'lnst. oj'Org.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
2
2
2

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…Previous findings carried out on P. ficiformis revealed the predominance of phospholipids (phosphatidyl ethanolamines PE, phosphatidylcholin PC, phosphatidylglycerols PG, phosphatidylserine PS and phosphatidylinositols PI), along with other constituents related to bacterial component (9-hexadecenoic, 15-methyl-9-hexadecenoic and l-octadecenoic acid) 103 . A single survey on C. reniformis highlighted the presence of 57 fatty acids, some of which with an odd number of carbon atoms putatively of bacterial origin 104 , while for C. nucula , the only one published work revealed that 5,9,23-triacontatrienoic acid was the more relevant lipid compound 105 . In the present study, the four sponge species were characterized by the presence of a “core metabolome” (lipids shared among all samples) represented in order of relative importance by phosphatidylcholines (PC), triglycerides (TG), phosphatidylethanolamines (PE), ceramides (Cer) and diglycerides (DG).…”
Section: Discussionmentioning
confidence: 99%
“…Previous findings carried out on P. ficiformis revealed the predominance of phospholipids (phosphatidyl ethanolamines PE, phosphatidylcholin PC, phosphatidylglycerols PG, phosphatidylserine PS and phosphatidylinositols PI), along with other constituents related to bacterial component (9-hexadecenoic, 15-methyl-9-hexadecenoic and l-octadecenoic acid) 103 . A single survey on C. reniformis highlighted the presence of 57 fatty acids, some of which with an odd number of carbon atoms putatively of bacterial origin 104 , while for C. nucula , the only one published work revealed that 5,9,23-triacontatrienoic acid was the more relevant lipid compound 105 . In the present study, the four sponge species were characterized by the presence of a “core metabolome” (lipids shared among all samples) represented in order of relative importance by phosphatidylcholines (PC), triglycerides (TG), phosphatidylethanolamines (PE), ceramides (Cer) and diglycerides (DG).…”
Section: Discussionmentioning
confidence: 99%